Factors associated with breastfeeding in children less than one year of age in the city of Cartagena, Colombia (Colombia Medica, 2024)
Introduction: The practice of breastfeeding represents multiple benefits to children; however, several studies show that there has been a gradual loss of breastfeeding habits in industrialized and developing countries, mainly because the great diversity of types of milk. Additionalliy, there was the presence of biological and socio-cultural factors, which influence and modify this practice and generate a negative impact on the health of the infant population. In Colombia, in 2005, it was reported that the median duration of exclusive breastfeeding was 2.2 months and the median duration was 14.9 months total; likewise, the department of Bolivar reported a median slightly over a month.Objective: To determine the relationship between social and biological factors in the prevalence of exclusive breastfeeding in children under one year of age in Cartagena, Colombia. Materials and methods: Cross-sectional study, the population consisted of the mothers of 23,109 children less than one year of age, the sample was 562 mothers. The probability sampling was stratified by clusters of three locations in the city where every neighborhood was a cluster. After selecting the neighborhood, a simple random sampling was conducted by city blocks. Mothers of children under one year of age were sought in their homes in the city blocks selected. The information was collected through the survey «Breastfeeding and complementary feeding» used by PROFAMILIA, demographic characteristics were demographic characteristics were also investigated.Results: The median for breastfeeding was 2 months, social factors associated were: not using a feeding bottle (CI: 2.37-5.38), nuclear family membership (CI: 1.29-2.72), not being a mother head of household (CI: 0.27-0.62), and the biological factor showing association was temporary suspension of breastfeeding (CI: 0.23-0.70).Conclusion: The duration of the exclusive breastfeeding practice among women turned out to be very short and the practice until the sixth month of life for their children was low. It was found that children born through caesarean section had a higher prevalence of maternal of maternal breastfeeding than those born vaginally.